Visualisasi Proses Vulkanisme melalui Media Pembelajaran Animasi berbasis Augmented Reality sebagai Media Digital Geografi - Salsabila, Alifah; Putra, Alfyananda Kurnia (Jayapangus Press, 2024)
Technological developments have experienced rapid progress which has an impact on the field of education. Technology is also a means of digital media in delivering material to students. This research developed an Augmented Reality (AR) in the form of the VULK-AR application as digital geographic media. The VULK-AR application is a new innovation in the process of volcanism and 3 types of volcanoes by combining various components in it. This research aims to explore the potential of Augmented Reality-based animation learning media and visualize the process of volcanism. This development uses the Research and Development (R&D) method with the SAM 1 model. Through the integration of AR with geography content, students can understand natural phenomena directly, and enable active learning experiences. The validation test results show that media experts provide a feasibility percentage of 92.84%, and material experts 89.55%. Product trials were carried out on teachers, the percentage obtained was 84.61% and students were 89.75%. The advantages of the VULK-AR application in geographic digital media can foster innovation in the field of technology in geography learning. It is hoped that this research can make a positive contribution in the development of digital geographic media on volcanism material.